Exploring the locational aspect of equitable accessibility to e-commerce deliveries: a study for brazilian cities - SOUSA, Luísa Tavares Muzzi de (2025)
E-commerce use increased in the last years. Each e-commerce delivery can be destined to the home or workplace of the buyer, or to Collection and Delivery Points (CDPs). E-commerce deliveries can increase accessibility to goods by benefiting those who face difficulties accessing traditional retail. However, accessibility to e-commerce deliveries is not equitable. Studies show that income and access to technology impact accessibility to delivery services. Logistics operational patterns and freight journeys are also influenced by locational characteristics such as street network connectivity, urban accessibility, populational density and land use. However, equity is a theme little explored in urban freight transport literature, especially in the context of the impact of locational characteristics of the residence place in accessibility to e-commerce deliveries. Therefore, this thesis aims to analyse the population’s accessibility to e- commerce deliveries in Brazilian cities. In this context, the thesis (i) identified the research gaps and factors to be considered in an equity analysis involving e- commerce; (ii) explored the locational factors influencing accessibility to e-commerce deliveries in Belo Horizonte and Recife, recognizing the spatial inequities in opportunity and identifying infrastructural and morphological factors related to home delivery accessibility; (iii) combined traditional logistics techniques with equity concepts and distributive justice principles to propose a CDP network for Belo Horizonte that could help lessen delivery accessibility inequities, and (iv) identified vulnerable areas related to the locational characteristics for priority in CDP location. Findings demonstrate that (i) current literature about equity in accessibility to e-commerce deliveries lacks clear equity definitions; (ii) lower levels of accessibility to home delivery services are associated with low street network density, unpaved and partially paved streets, high populational density and less diverse land uses; (iii) the proposed CDP network could cover up to 97.6% of the population, including 94.8% of low-income households, and (iv) from a total of 311 CDPs proposed, 77 should be prioritized for implementation to serve vulnerable areas. Finally, this thesis demonstrates the importance of considering equity in accessibility analyses in urban freight transport and could serve as a guide for public policies regarding e-commerce delivery accessibility.